RISK OF URBAN DEVELOPMENT IN MINED AREAS AND GEOMATICS ANALYSIS, CASE STUDY OF THE MIGUEL HIDALGO MUNICIPALITY, CDMX - Rivera, Oscar Daniel (2025)
The existing problem of self-constructions in mined areas is something historical in certain areas of the Mexican Republic, becoming a latent risk of collapse in some houses built in Mexico City (CDMX). It is important to understand that many constructions omitted the characteristics of the soil, therefore, the objective is to identify sinkholes according to data from the Secretariat of Integral Risk Management and Civil Protection of the CDMX, investigating what happened in the municipality Miguel Hidalgo derived from the constant collapse of mines examining with Geographic Information Systems (GIS) and geomatics, with the purpose of reinforcing structures in high-risk zones and limiting their urban growth, which could be replicated in other parts of Latin America where the geographical, economic and social characteristics are similar to the study area.